Seawater carbonate chemistry and properties of the exoskeleton in adult Tanner crabs, Chionoecetes bairdi - Dickinson, Gary H; Bejerano, Shai; Salvador, Trina; Makdisi, Christine; Patel, Shrey; Long, W Christopher; Swiney, Katherine M; Foy, Robert J; Steffel, Brittan V; Smith, Kathryn E; Aronson, Richard B (PANGAEA, 2023)
Ocean acidification can affect the ability of calcifying organisms to build and maintain mineralized tissue. In decapod crustaceans, the exoskeleton is a multilayered structure composed of chitin, protein, and mineral, predominately magnesian calcite or amorphous calcium carbonate (ACC). We investigated the effects of acidification on the exoskeleton of mature (post-terminal-molt) female southern Tanner crabs, Chionoecetes bairdi. Crabs were exposed to one of three pH levels—8.1, 7.8, or 7.5—for two years. Reduced pH led to a suite of body-region-specific effects on the exoskeleton. Microhardness of the claw was 38% lower in crabs at pH 7.5 compared with those at pH 8.1, but carapace microhardness was unaffected by pH. In contrast, reduced pH altered elemental content in the carapace (reduced calcium, increased magnesium), but not the claw. Diminished structural integrity and thinning of the exoskeleton was observed at reduced pH in both body regions; internal erosion of the carapace was present in most crabs at pH 7.5, and the claws of these crabs showed substantial external erosion, with tooth-like denticles nearly or completely worn away. Using infrared spectroscopy, we observed a shift in the phase of calcium carbonate present in the carapace of pH-7.5 crabs: a mix of ACC and calcite was found in the carapace of crabs at pH 8.1, whereas the bulk of calcium carbonate had transformed to calcite in pH-7.5 crabs. With limited capacity for repair, the exoskeleton of long-lived crabs that undergo a terminal molt, such as C. bairdi, may be especially susceptible to ocean acidification.
Keywords: Animalia; Arthropoda; Benthic animals; Benthos; Biomass/Abundance/Elemental composition; Calcification/Dissolution; Chionoecetes bairdi; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Growth/Morphology; Laboratory experiment; North Pacific; Other studied parameter or process; Single species; Temperate